The Effect of Education, Training and Work Experience on Work Productivity With Work Motivation as a Mediator (Empirical Study of Private Employees inThe Automotive Industry in Tangerang) - Cindy Yonuari (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
This study aims to examine the effects of education, training, and work experience on job productivity, with work motivation acting as a mediating variable. A quantitative research approach was applied, focusing on private sector employees in the automotive industry in Tangerang as the unit of analysis. Data were collected through questionnaire distribution and analyzed using SmartPLS version 3. Since the population size was not clearly defined, the sample was determined using Hair’s method, which suggests multiplying the number of indicators by a factor between 5 and 10. With 35 indicators multiplied by 8, a total of 280 respondents were obtained. The data analysis process involved both outer model and inner model evaluations. The outer model assessment included tests of validity, reliability, discriminant validity, and collinearity, while the inner model evaluation covered R-square, F-square, bootstrapping, path coefficients, and specific indirect effects. The results reveal that education and training do not have a significant effect on job productivity. In contrast, work experience and work motivation show a positive and significant influence on job productivity. Additionally, work motivation does not significantly mediate the relationship between education and training and job productivity. However, it significantly mediates the relationship between work experience and job productivity in a positive direction. These findings suggest that work experience and work motivation are the key determinants of job productivity in the automotive industry in Tangerang.